2017
DOI: 10.1530/eje-16-1079
|View full text |Cite
|
Sign up to set email alerts
|

Association between neuroendocrine tumors biomarkers and primary tumor site and disease type based on total 68Ga-DOTATATE-Avid tumor volume measurements

Abstract: Objective To determine the association between neuroendocrine tumor (NET) biomarker levels and extent of disease as assessed by 68Ga DOTATATE PET/CT imaging. Design A retrospective analysis of a prospective database of patients with NETs. Methods Fasting plasma chromogranin A (CgA), neuron-specific enolase (NSE), gastrin, glucagon, vasoactive intestinal peptide (VIP) and pancreatic polypeptide (PP), and 24-hour urinary 5-hydroxyindoleacetic acid (5-HIAA) levels were measured. Correlation between biomarkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 30 publications
5
28
0
Order By: Relevance
“…Bone FD has been visualized with conventional SSTRs scintigraphy using 111 ln-pentetreotide, suggesting cell surface over-expression of SSTRs by fibrous dysplastic cells (119). The introduction of 68 Ga-DOTA-conjugated-peptides into clinical practice has enabled the employment of PET-imaging in targeting lesions, characterized by SSTRs-overexpressi on (18,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Papadakis et al reported intensely increased 68 Ga-DOTATE (radiolabeled somatostatin analogue suitable for PET-imaging, which targets SSTRs) activity on PET/CT, by a biopsy proven FD lesion in the temporal bone (22).…”
Section: Fibrous Dysplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…Bone FD has been visualized with conventional SSTRs scintigraphy using 111 ln-pentetreotide, suggesting cell surface over-expression of SSTRs by fibrous dysplastic cells (119). The introduction of 68 Ga-DOTA-conjugated-peptides into clinical practice has enabled the employment of PET-imaging in targeting lesions, characterized by SSTRs-overexpressi on (18,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Papadakis et al reported intensely increased 68 Ga-DOTATE (radiolabeled somatostatin analogue suitable for PET-imaging, which targets SSTRs) activity on PET/CT, by a biopsy proven FD lesion in the temporal bone (22).…”
Section: Fibrous Dysplasiamentioning
confidence: 99%
“…68 Ga-DOTA-compounds are somatostatin (SST) analogs, radiolabeled with the positron emitting isotope gallium-68 ( 68 Ga) through the chelator 1,4,7,10-tetraazacyclododecane-1, 4,7,10-tetraacetic acid (DOTA) (18). The employment of these compounds enables highly efficient targeting of lesions which are characterized by cell-surface over-expression of SST receptors (SSTRs), such as neuroendocrine tumors (NETs), for which PET/CT imaging with 68 Ga-DOTA-compounds is evolving as the imaging standard of reference (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Secretion of chromogranin A into blood is fairly ubiquitous across NENs [34] and is therefore unlikely to be of assistance in determining the primary site once a histological diagnosis is made. 24-h urinary 5-hydroxyindoleacetic acid, a break-down product of serotonin is more commonly raised in small intestinal NENs with high levels associated with metastatic disease [35].…”
Section: Biochemical Testsmentioning
confidence: 99%
“…Furthermore, false positives may be expected in metastatic lymph nodes, meningiomas, and inflammation foci ( 21 ). Recently, novel 68 Gallium ( 68 Ga)-DOTA-labeled somatostatin analogs ( 68 Ga-DOTATATE, 68 Ga-DOTANOC, and 68 Ga-DOTATOC) have been introduced to clinical PET/CT use; they are reported to have higher sensitivity for detecting neuroendocrine tumors compared to “classic” SRS ( 25 ) ( Figure 1 ). 68 Ga-DOTATATE PET/CT was better than 18 F-DOPA, 18 F-FDA PET/CT, CT/MRI, and especially 18 F-FDG PET/CT in imaging patients ( n = 22) with sporadic metastatic PHEO/PGL ( 26 ), or head and neck PGLs (sensitivity reported at 93% in a series of 30 patients) ( 20 ).…”
Section: Functional Imaging In Patients With Pheo/pglmentioning
confidence: 99%